Taxonomic and phylogenic appraisal of a novel species and a new record of Stictidaceae from coffee in Yunnan Province, China - Lu, Li; Tibpromma, Saowaluck; Karunarathna, Samantha C.; Thiyagaraja, Vinodhini; Xu, Jianchu; Jayawardena, Ruvishika S.; Lumyong, Saisamorn; Hyde, Kevin D. (Phytotaxa, 2021)
Coffee, an important economic crop, is often threatened by fungal infections. During a survey of coffee fungi in Yunnan Province, China, two saprobic Stictidaceae species were collected. Maximum likelihood (ML) and Bayesian posterior probability of combined LSU, ITS and mtSSU genes supported the placement of our fungal collections within Fitzroyomyces and Ostropomyces with high statistical support. A new species, Fitzroyomyces yunnanensis sp. nov. and a new record, Ostropomyces pruinosellus are introduced. These two species were recorded on coffee wood in sexual and asexual states, respectively. Their taxonomic placements were further supported by detailed morphological and phylogenetic comparisons of allied taxa.